CARE GIVING RESPONSIBILITES FOR CHILDREN LIVING WITH HIV/AIDS in CITY OF BANDUNG - Ayi Haryani (SAMPURASUN, 2017)
Objective: The HIV/AIDS epidemy on Children have devastating impacts on the survival and development of the children. Limited availability and access to government services, stigma and discrimination, as well as the absence and declining abilities of parents in meeting the needs of the children living with HIV/AIDS (CLWHA) raises the risk for those children to experience severe neglect. The purpose of this study is to examines the responsibilities of child care and to identify those who carry out the role of parenting for children with HIV/AIDS in Bandung. Methods: This study applies descriptive method, with a qualitative approach. Indept Interviews conducted on social workers in four service providers institutions for people with HIV / AIDS in the city of Bandung. Results: 29 out of 46 (56%) CLWHA that gets assistance from service providers have lost one or both parents. There are 17 couples of PLWHA parents and caregivers could not fully functions as providers for the needs of their children, due to their health conditions that gradually decreased, complexity of their drug regimens, stigma and fear that associated with death, and also have to care for their families. There is only 11 parents who continue to carry out their parenting responsibilities and roles. While 35 of CLWHA, sequentially, cared by grandparents, or aunts/uncles as relatives that most widely taken over the responsibilities and roles of caregiving. They do this with the main reason for the absence and the inability of parents because of health problems, behavioral, and economic capacity of the family. The existence of strong emotional bond amongs the extended family, and the intention to protect family honors also has prevents family from handing over the childcare to outsiders, which then prevents the child from being abandoned. Conclusion: This study showed that limited availability and adequacy of governmental services, stigma and disriminasi, absenteeism and the poor capacity of the parents, does not directly cause severe neglect for CLWHA. Traditional cultural values related to extended family life have strengthened the role of the nuclear family and relatives to maintain their parenting responsibilities on children of their relatives.